The craftsman in America - National Geographic Society (U.S.). Special Publications Division (Washington : The Society, 1975)
Explains the history of handicrafts in the United States including examples of work by silversmith, Paul Revere; carpenter, Seth Story; embroidery worker, Mary Foot and many others
Homeland and handwork / C. Malcolm Watkins -- In the American grain / Tom Melham -- A nautical portfolio / Tom Melham -- From the American earth / Andy Leon Harney -- Fiber and fabric / Cynthia Russ Ramsay -- In the mountains / Clay Anderson -- Toys : a portfolio of magic / Beverly Spotswood -- The scene today / Patricia L. Raymer
Includes bibliographical references and index
Keywords: Handicraft -- United States; Artisans -- United States; Handicraft -- United States